Commercial hospitality as a business model in the independent hotel company - Kowalski, Zbigniew (Managerial Economics, 2014)
The hospitality business, not only in Poland, especially the independent hotel companies, require a greater commitment from theorists and practitioners in industry and others, who can inspire them with their knowledge, competence and experience. The presented for the first time in Poland example of using the commercial hospitality for more effective and profitable hotel operation is the process innovation itself becoming a new way of organizing the service activity of the hotel. One need to keep in mind that this is “a continuous process, consisting of a series of incremental changes in products and processes [and] this may occasionally complicate the identification of innovations in services in terms of single events” [7, s. 38], e.g. the individual implementations. Commercial hospitality as a business model could be an innovative tool in the hands of the hotel manager of the independent hotel company, because it allows him more effective control over the process of service provision and the creation of the value chain starting from inviting guest until bidding them farewell. Commercial hospitality mustn’t be perceived as the added value as it is the integral element of the full value of the service expressed in the price and paid by the client or guest. The phenomenon of commercial hospitality, not only in Poland, is a relatively young research issue and that is why it is the subject to constant assessment, analysis and constructive criticism. However, it is important that this publication enables a greater understanding of and commitment to the commercial hospitality. Goodwill for commercial hospitality and the innovative approach to the commercial hospitality management are the vector indicated by author in improving hotel’s resistance to competition and in the process of development of the independent hotel companies of the XXI century.